KEEFEKTIFAN MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION PENDEKATAN JOYFUL LEARNING TERHADAP KEMAMPUAN PENALARAN MATEMATIS PADA MATERI TEOREMA PYTHAGORAS KELAS VIII - Nike Andriani; Venissa Dian Mawarsari; Eko Andy Purnomo (Universitas Muhammadiyah Semarang, 2017)
The problems in this study appears is the low ability of students mathematical reasoning which is characterized most of learners difficulties in solving implementation problems to change contextual problems into mathematical form. In addition, students the activeness and interest is still low. One way to overcome these problems is to implement cooperative learning model “Cooperative Integrated Reading and Composition (CIRC) ”Joyful Learning approach. This study aims to identify using a mathematical model of CIRCJoyful Learning approach the ability of mathematical reasoning of learners effective. This research was anexperiment research, with every grade VIII students of SMP Muhammadiyah 3 Semarang academic year 2017/2018 as the population.The samples in this reasearch were class VIII B as experimental class, classVIII D as control class, and class VIII C as test class. The results of thisstudy indicate that: (1) learners using CIRCJoyful Learning approach applied reach of 93,33% more than 81% with the completeness criterion 75, (2) the effect test showed the influence of activity towards and interest the mathematical reasoning in application of learning model CIRCJoyful Learning approach by 88,6%. (3) Different test results indicate there is difference of average ability of comprehension of mathematical reasoning between using learning model of CIRCJoyful Learning approach by 82,00 with using ekspository learning model equal to 78,73. Based on these three things, it shows that the applying of learning model CIRC Joyful Learning approach on the ability of mathematical reasoning of effective classpythagoras theorem material.Keywords: Cooperative Integrated Reading and Composition, joyfullearning, reasoning mathematically